Boosting the efficiency of carbon-based planar CsPbBr3 perovskite solar cells by a modified multistep spin-coating technique and interface engineering - Liu, Xingyue; Tan, Xianhua; Liu, Zhiyong; Ye, Haibo; Sun, Bo; Shi, Tielin; Tang, Zirong; Liao, Guanglan (Nano energy, 2019)
All-inorganic CsPbBr3 perovskite solar cells (PSCs) have attracted tremendous attentions in the photovoltaic field these days in view of their outstanding stability, especially thermal stability. However, the bromide-rich perovskite, such as CsPbBr3, always suffer from a low phase-purity and poor morphology synthesized by traditional two-step deposition route. Herein, we demonstrate a facile multistep spin-coating strategy to fabricate high-quality CsPbBr3 films on the low-temperature processed compact TiO2 (c-TiO2) electron transport layer (ETL) of the carbon-based PSCs. As-prepared films exhibit more homogeneous with higher CsPbBr3-phase purity and larger average grain sizes up to 1 µm, compared to those prepared through traditional two-step deposition process. The champion power conversion efficiency (PCE) of the planar CsPbBr3 PSC is boosted from 7.05% to 8.12%, getting an increase by 15.2%, due to the increased crystallinity and light-harvesting ability as well as reduced trap states of the CsPbBr3 film. To further enhance the device performance, a SnO2 thin layer with much higher carrier mobility than TiO2 is introduced to passivate the c-TiO2 ETL. It is found that the SnO2 layer can not only improve the surface morphology of the ETL, but also reduce the current shunting pathways in the c-TiO2. The TiO2/SnO2 bilayered ETL possesses a superior electron extraction capability, beneficial to the charge transport and suppression of the interfacial trap-assisted recombination. The best-performing TiO2/SnO2-based CsPbBr3 PSC delivers an excellent fill factor of 0.817 and a high PCE of 8.79%, which is the highest efficiency for planar CsPbBr3 PSCs reported to date. More importantly, the unencapsulated all-inorganic PSCs show a promising humidity and thermal stability with no decline in efficiency when stored in ambient air at room temperature (25 °C) for over 1000 h and 60 °C for one month, respectively. Our work pave the ways for practical applications of cost-effective, highly efficient and stable all-inorganic PSCs. Boosting the efficiency of carbon-based planar CsPbBr3 perovskite solar cells by a modified multistep spin-coating technique and interface engineering is demonstrated. A champion power conversion efficiency (PCE) of 8.79% is obtained for the as-prepared PSCs, which is the highest efficiency for planar CsPbBr3 PSCs reported yet. [Display omitted] •The highest efficiency (8.79%) among planar CsPbBr3 perovskite solar cells that has ever been reported is achieved.•A novel multistep spin-coating technique to prepare CsPbBr3 films with high phase-purity and crystallinity is proposed.•A SnO2 thin layer is introduced to passivate the TiO2 surface and enhance the electron extraction capability of the ETL.•Cost-effective and highly stable CuPc and carbon are introduced as HTL and counter electrode, respectively.•Low manufacturing costs as well as excellent moisture and thermal stability are obtained for the as-prepared devices.